Diagnosis and treatment of müllerian malformations - Itana de Mattos Pinto e Passos; Renata Lopes Britto (Taiwanese Journal of Obstetrics & Gynecology, 2020)
Anomalies in the müllerian ducts are congenital alterations with more prevalence than it is imagined, varying from 0.5 to 6.7% in the general population and up to 16.7% in women with recurrent miscarriage. The main findings are primary amenorrhea, dysmenorrhea, pelvic pain, endometriosis, sexual difficulties and low self-esteem. The major impact on the quality of life in women stricken by these problems justifies this study, whose objective is to analyze their most important aspects such as etiopathogeny, classification, diagnostic methods and proposed treatments. The research was performed on the Medline-PubMed database from 1904 to 2018. The American Fertility Society, European Society of Human Reproduction and Embryology, and the European Society of Gynaecological Endoscopy classify malformations as: Class 1/U5bC4V4: agenesis or hypoplasia of uterus and vagina; Class 1/U5aC4V4: cervical hypoplasia, associated with total or partial vaginal agenesis; Class 2/U4: unicornuate uterus; Class 3/U3bC2V1 or Class3/U3bC2V2: uterus didelphys; Class 4/U3C0: bicornuate uterus; Class 5/U2: septate uterus; Class 6: arcuate uterus; Class 7/U1: induced by diethylstilbestrol, represented by a T-shaped uterus; and V3: transverse vaginal septum. The diagnostic methods are the two-dimensional or three-dimensional ultrasound, MRI, hysterosalpingo-contrast-sonography, X-ray hysterosalpingography, hysteroscopy and laparoscopy. Some müllerian malformations are healed with surgery and/or self-dilatation. For vaginal agenesis, dilatation by Frank technique shows good results while malformations with obstruction of the menstrual flow need to be rapidly treated by surgery. Keywords: Genital anomalies, Müllerian malformations, Pelvic pain, Primary amenorrhea, Vaginal agenesis